Effects of Recognition of Prior Learning on Job Market Outcomes : Impact Evaluation in Bangladesh - Nakata, Shiro; Sharma, Uttam; Rahman, Tashmina; Rahman, Mokhlesur; Aziz, Mustahsin-Ul (World Bank, Washington, DC, 2021)
The recognition of prior learning provides opportunities for workers to have their skills assessed and certified. In many countries, recognition of prior learning is expected to broaden individuals’ empowerment and economic opportunities. Using a randomized control trial method, this impact evaluation study aims to assess whether and to what extent assessment and certification of prior learning effectively improve economic and other job outcomes among assessment participants in Bangladesh. Five hundred applicants were randomly assigned to the treatment group and 500 applicants to the control group. The baseline survey took place in June 2018 and the end-line survey in January 2019. The findings indicate that assessment prior learning positively impacts workers’ employment outcomes and quality of employment, including the chance of getting employed, wage levels, formality of employment, and workers’ confidence in their skills and jobs. The findings also suggest that women may benefit more than men from certificates of recognition of prior learning in Bangladesh. The transition analysis further supports the finding that recognition of prior learning facilitates the transition of unemployed or not-working workers into employment. Recognition of prior learning also increases the chances of finding work through formal job search channels and at formal and larger private companies. These findings align with the assumption and expectation behind the recognition of prior learning programs in the context of economic development. The participants in assessments and certification of prior learning had overwhelmingly positive opinions about them. The study has some limitations and suggestions for future research.